Privacy in the age of big data recognizing threats, defending your rights, and protecting your family - Payton, Theresa 1966-; Claypoole, Ted 1963- (Rowman & Littlefield, 2014)
"Privacy in the Age of Big Data highlights the many positive outcomes of digital surveillance and data collection, while also outlining those forms of data collection to which we do not always consent, and of which we are likely unaware, as well as the dangers inherent in such surveillance and tracking. Theresa M. Payton and Theodore Claypoole skillfully introduce readers to the many ways we are "watched" and how to change behaviors and activities to recapture and regain more of our privacy."--Book jacket.